Sistem Deteksi Hipoksia menggunakan Metode Decision Tree berdasarkan Detak Jantung dan Kadar Oksigen - Elisabeth Agustina; Edita Rosana Widasari; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Hypoxia is a condition where there is a continuous lack of oxygen either in the short or long term according to a period. If hypoxia occurs in the short term, what is caused is acute hypoxia. The symptoms found in hypoxia are very fast heartbeat (tachycardia), rapid breathing, dizziness, weakness. Based on the existing problems, the authors want to conduct research to detect hypoxia. The tool designed for this study can detect hypoxia based on heart rate and oxygen saturation. This detection is very easy to use, just by placing your index finger on the MAX30100 infrared sensor, after that you get the measurement results which will be displayed on the LCD screen. The results of these measurements will be the input data for classification. This classification uses the Decision Tree method where this method is very accurate and fast in carrying out the classification process. Classification results will be displayed on the LCD screen. Testing of this tool was carried out 10 trials in detecting heart rate and oxygen saturation. The accuracy obtained when doing the classification is 100%. The MAX30100 sensor when measuring heart rate obtains an accuracy of 97.66% and an error rate of around 2.34. Then, the accuracy obtained when detecting oxygen levels is 98.75% with an error rate of 1.25%